UPAYA MENINGKATKAN KEMAMPUAN BAHASA INGGRIS UNTUK ANAK USIA DINI DENGAN METODE GERAK DAN LAGU (Penelitian Tindakan Kelas di Kelompok B RA Al Hidayah Rancah Kabupaten Ciamis) - Sri Utari (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Based on the observations that have been made, this research is motivated by the low English language skills of early childhood in RA Al Hidayah, Dusun Sindangjaya, Cisontrol Village, Rancah District. The problem to be solved in this study is whether the motion and song method can improve English language skills in children of group B RA Al Hidayah, Dusun Sindangjaya, Cisontrol Village, Rancah District. This type of research is classroom action research (CAR) using 2 cycles. Each cycle consists of planning, implementation, observation and reflection. The research subjects were the children of group B RA Al Hidayah, Dusun Sindangjaya, Cisontrol Village, Rancah District, totaling 11 children, consisting of 9 boys and 2 girls. The data collection techniques used in this study were observation techniques, test techniques, documentation techniques and descriptive analysis. Based on the results of learning using motion and song methods to improve children's English skills in cycle 1, the success only reached 8 people (72.72%) of 11 children who were active in singing well, 4 people (36.36%) of 11 children who serious in singing well, and 4 people (36.36%) out of 11 children who memorized English vocabulary well. In cycle 2, each indicator that is considered to have increased quite well, there are 10 people (90.9%) of 11 children who are active in singing well, 8 people (72.72%) of 11 children who are serious in singing well, and 9 people (81.81%) from 11 children who memorized English vocabulary well. Based on the analysis in cycle 2, the expected value has been achieved. Researchers can conclude that the use of motion and song methods can improve the English skills of children in group B, RA Al Hidayah, Sindangjaya Hamlet, Cisontrol Village, Rancah District.